Equivalencia y valor en procesos de reciprocidad e intercambio entre los mapuches - Julio Tereucán-Angulo; Claudio Briceño-Olivera; José Gálvez-Nieto (Universidad Autónoma del Estado de México, 2016)
Reciprocity and exchange are two issues of interest in anthropology stated in Marcel Mauss essay about gifting. However, this topic has had limited attention among the Mapuche, especially within the area of social practices that people and domestic groups perform in rural communities. The objective of this article is the analysis of reciprocity and exchange from the perspective of interchangeability and associated processes in Mapuche communities, to later evaluate the principles involved, especially the ones related to the equivalence and value of reciprocity; postulating that based on the analysis the following can understood: practices of social organization, economic relations, everyday social interactions between domestic groups, among other areas. The research was conducted with a qualitative strategy, and the ethnographic method was developed to process data collection in Mapuche communities of southern Chile.